2020
DOI: 10.1111/jpn.13463
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of hepatic methionine catabolic enzyme activities (Transmethylation and Transsulphuration) and associated physiological amino acids in E10‐21 chick embryos and D1‐49 broilers

Abstract: Developmental changes in hepatic methionine adenosyltransferase, cystathionine β-synthase, cystathionase, and glycine N-methyltransferase were determined in broiler chick embryos and hatched chicks by using radiometric and spectrometric methods. Hepatic free methionine, S-adenosylmethionine, S-adenosylhomocysteine, homocysteine, cystathionine, and cysteine levels were also investigated. Results showed an increase in hepatic MAT activity from E10 to E21 during embryogenesis, suggesting greater transmethylation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
(113 reference statements)
0
4
0
Order By: Relevance
“…(1996) reported that a vitamin B 6 deficiency may contribute to impaired transsulfuration in humans, in accordance with the response of plasma concentration of homocysteine, cystathionine, and cysteine after a methionine load. The finding of unchanged cysteine (M + 3/M + 0) in 18-day-old chick embryos from breeders fed without pyridoxine supplementation may be attributed to a limited transsulfuration ability in chick embryos suggested by Lu et al., 2020a , Lu et al., 2020b . Moreover, in accordance with the dissociation constants of CBS (0.7 umol/L) and SHMT (27.5 umol/L) ( Jones and Priest, 1978 ; Kery et al., 1999 ), it seems that during vitamin B 6 deficiencies, the SHMT can be affected, but little or no effect on CBS is observed.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…(1996) reported that a vitamin B 6 deficiency may contribute to impaired transsulfuration in humans, in accordance with the response of plasma concentration of homocysteine, cystathionine, and cysteine after a methionine load. The finding of unchanged cysteine (M + 3/M + 0) in 18-day-old chick embryos from breeders fed without pyridoxine supplementation may be attributed to a limited transsulfuration ability in chick embryos suggested by Lu et al., 2020a , Lu et al., 2020b . Moreover, in accordance with the dissociation constants of CBS (0.7 umol/L) and SHMT (27.5 umol/L) ( Jones and Priest, 1978 ; Kery et al., 1999 ), it seems that during vitamin B 6 deficiencies, the SHMT can be affected, but little or no effect on CBS is observed.…”
Section: Discussionmentioning
confidence: 94%
“…The synthesis of cysteine from serine and homocysteine via transsulfuration pathway is catalyzed by cystathionine ß-synthase (EC 4.2.1.22) and cystathionase, and both of these enzymes require vitamin B 6 . Lu et al. (2020b) recently reported lower levels of cystathionine ß-synthase in the E10-E21 embryo liver and from day 1 to day 7 in the liver of hatched chicks compared with cystathionine ß-synthase in 35 to 49 d broilers.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations